Chia musilage coating: Applications with gojiberry extract for shelf life extension of Oncorhynchus mykiss and it's antibacterial and oxidative effects - Coban, Ozlem Emir; Ergur, Nuran (Wiley, 2021)
The present study was carried out to evaluate chia mucilage coating and goji berry extract as preservative agents in filleted trout during storage for 18 days at 4celcius. The trout fillets were separated into four lots and applied the following treatments by immersion processing: I) Control (without coating), II) Chia (Ch), III) Chia + 1% Goji berry extract (Ch + 1GE), and IV) Chia + 2% Goji berry extract (Ch + 2GE), then stored for 18 days at 4 degrees C. Results demonstrated that microbial growth was delayed in 2%GE containing chia coated group. In addition, the chia coated samples retarded the increase in the contents of TVB-N, pH, and TBA during storage. In addition, shelf life of the samples stored at 4oC was determined as 3 days in control group, 15 days in groups of coated with Ch and Ch+1%GE and 18 days in group of coated with Ch+2% GE. Practical applications Quality of rainbow trout fillets was keeped by edible coating formed from chia seed musilage With the prepared coatings were inhibed oxidation and microbial growht during fillet storage. A high shelf life was determined by the coatings formulated with 1% gojiberry extract and 2% gojiberry extract. Chia musilage coating may be an alternative to other coatings in the coating of meat and meat products.
Keywords: Rainbow-Trout; Edible Films; Essential Oil; Quality; Seed; Stability